Small + Safe + Well: lessons learned from a Total Worker Health® randomized intervention to promote organizational change in small business - Natalie V. Schwatka; Miranda Dally; Erin Shore; Liliana Tenney; Carol E. Brown; Joshua G. Scott; Lynn Dexter; Lee S. Newman (BMC, 2022)
Abstract Background Leadership commitment to worker safety and health is one of the most important factors when organizations develop and implement a Total Worker Health® approach. We aimed to assess the effectiveness of a Total Worker Health ("TWH") leadership development program that targeted owners and other senior-level leadership positions on changing organizational and worker outcomes from baseline to one-year later. Methods The Small + Safe + Well study included small businesses from a variety of industries in the state of Colorado, USA that were participating in Health Links™. We designed a randomized waitlisted control comparison design (RCT) to evaluate the added benefit of a TWH leadership development program. An employer assessment tool was used to assess TWH policies and programs, and an employee health and safety survey was used to assess safety leadership and health leadership practices, safety climate and health climate, safety behaviors and health behaviors, and well-being. We used a linear mixed model framework with random effects for business and employee to assess the impact of intervention on the outcomes of interest. Results Thirty-six businesses (37% retention) and 250 employees (9% retention) met the RCT study inclusion criteria and were included in the analysis. Businesses improved their TWH policies and programs score from baseline to one-year later, regardless of leadership intervention group assignment. Neither intervention group demonstrated improvements in employee-reported outcomes. Conclusions This study sought to address a gap in the literature regarding small business senior leadership development for TWH. Our study demonstrates many of the challenges of conducting studies focused on organizational change in workplaces, specifically in small businesses. When designing TWH intervention studies, researchers should consider how to best engage small business leaders in interventions and implementations early on, as well as methods that are well matched to measuring primary and secondary outcomes longitudinally. Future research is needed to test the feasibility and sustainability of TWH interventions in small business. Trial registration The trial was retrospectively registered with ClinicalTrials.gov ( ID U19OH011227 ).